2018
DOI: 10.21873/anticanres.12822
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Characterization of a Novel Human Clear-cell Sarcoma of Soft-tissue Cell Line, RSAR001, Derived from Pleural Effusion of a Patient with Pleural Dissemination

Abstract: These findings indicate that the RSAR001 cell line harbors EWSR1-ATF1 type 1 chimeric fusion gene, which is specific to CCS. RSAR001 cells might be useful for investigating biological behaviors and developing new treatments such as molecular-targeting antitumor drugs or immunological drugs for CCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In most cases, CCS cells have a strong immuno-histological staining of HMB-45, melan-A, and S100 [96]. The detection of translocation has been confirmed by PCR and sequencing in several studies [97][98][99][100]; however, no major study of monitoring disease activity via liquid biopsy has been reported. As the survival rates for CCS are~40% at 10 years compared to~60% at five years [101], long-term liquid biopsy surveillance may improve patient outcomes for this slow-growing tumour.…”
Section: Clear Cell Sarcoma Of Soft Tissuementioning
confidence: 98%
“…In most cases, CCS cells have a strong immuno-histological staining of HMB-45, melan-A, and S100 [96]. The detection of translocation has been confirmed by PCR and sequencing in several studies [97][98][99][100]; however, no major study of monitoring disease activity via liquid biopsy has been reported. As the survival rates for CCS are~40% at 10 years compared to~60% at five years [101], long-term liquid biopsy surveillance may improve patient outcomes for this slow-growing tumour.…”
Section: Clear Cell Sarcoma Of Soft Tissuementioning
confidence: 98%